Linking recognition practices and national qualifications frameworks : international benchmarking of experiences and strategies on the recognition, validation and accreditation (RVA) of non-formal and informal learning - Singh, Madhu [Herausgeber]; Duvekot, Ruud [Herausgeber] (UNESCO Institute for Lifelong Learning, 2013)
"Qualification systems across the globe are generally well equipped to deal with learning acquired in institutional settings. However, one of the greatest challenges is how to recognise learning that occurs outside the formal education sector. In this book, the recognition, validation and accreditation (RVA) of learning in formal, non-formal and informal settings is examined within a variety of national und regional contexts. It contains 23 country specific reports on the linkages between national qualifications frameworks (NQFs) and the practices of RVA from all five UNESCO regions: Africa, the Arab States, Asia and the Pacific, Europe and North America, and Latin America and the Carribean. These reports are based on the outcomes of an international conference organised by the UNESCO Institute for Lifelong Learning in Hamburg in March 2010, entitled 'Linking recognition practices to qualification frameworks - North-South collaborative research'. In reviewing the implementation of RVA, this book focuses on 5 key factors: national reference points for RVA; policy and legislation; the contribution of recognition to social inclusion; stakeholder involvement; and features of recognition processes." (Editor, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; L 2.1.1 Informelles Lernen; I 2.3.1 Afrika; I 2.3.4 Asien; I 2.3.2 Nordamerika; I 2.3.3 Lateinamerika; I 2.2 Europa; Berufsbildung; Anrechnung von Bildungsleistungen; Nicht-formale Qualifikation; Informelles Lernen; Nationaler Qualifikationsrahmen; Afrika; Asien; Arabische Länder; Amerika; Lateinamerika; Europa